Transformation of the Watershed Basin of Udy River Within Kharkiv - Klieshch, A. A.; Maksymenko, N. V. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2019)
Purpose. To assess the extent of anthropogenic transformation of the landscape of watershed basin due to urban development and identify ways of normalizing the load on landscapes during the development of the city. Methods. In the course of the study, a set of methods was used: expert evaluation, cartographic methods (including cartometry operations) and geoinformation modeling of the relief. Results. In the course of the study, it was found that the urbogenic transformation of natural landscapes is primarily due to the formation of a system of land uses that prompts the replacement of the ecological functions of the landscape by public ones. The landscape differentiation of the catchment basin, based on geoinformation modeling of the terrain, made it possible to identify the spatial configuration and area of each of its subsystems. It was found that the floodplain subsystem occupies 8.47 %, the alluvial subsystem – 21.4 %, the slope subsystem – 17.49 %, and the watershed-plain – 52.64 % of the area of the studied catchment area. Conclusions. As a result of calculating the coefficients of transformation of land use types and their summation within each of the subsystems, it is established that the highest degree of transformation of landscapes has a watershed-plain subsystem. The average degree of transformation is characterized by the alluvial terrace and slope subsystems. The lowest index of anthropogenic transformation coefficient within the catchment area has a floodplain subsystem. For the territory of the floodplain, zoning of the territory according to the level of anthropogenic load on the landscape of the catchment area was carried out. Environmental measures are proposed for each of the zones.